Factors influencing use of analgesics among construction workers in the Ga-East municipality of the Greater Accra Region, Ghana - Badzi, C.D.; Ackumey, M.M. (Ghana Medical Journal, 2017)
BACKGROUND: Analgesics also known as painkillers are widely used for pain relief. There are severe health implications associated with excessive use of analgesics. This paper examines factors influencing the use of analgesics among construction workers in the Ga-East Municipality (GEM) of the Greater Accra region of Ghana. METHODS: This is a cross-sectional study involving 206 construction workers randomly sampled from 7 construction sites in the GEM. A structured questionnaire was used to elicit responses on knowledge of analgesics, types of analgesics used and factors influencing the use of analgesics. Chi-square test analysis was used to examine factors influencing analgesic use. RESULTS: The majority of workers were aged between 15 to 44 years (89.8%) and 51.9 percent of respondents had completed Junior high school. Many respondents (68.0%) used Brand 1 a locally manufactured analgesic with paracetamol, aspirin and caffeine as the active ingredients and 31.6 percent of respondents had no knowledge of possible side effects of continuous use of analgesics. Chi square analysis showed that age was significantly associated with use of analgesics (p<0.01). Knowledge of the types of analgesics, dosage and side effects did not influence use (p>0.05). Television and radio advertisements influenced use of analgesics (p<0.01). CONCLUSION: Knowledge on analgesic use and knowledge of probable serious side effects was inadequate. Pharmacists and chemists involvement in education of clients of the side effects of analgesics is highly recommended to minimise misuse. The Food and Drugs Authority should regulate the proliferation of advertisements for analgesics in the media.
Journal Article on Factors influencing the use of analgesics among construction workers
Keywords: analgesics; NSAIDs; construction workers; over-the-counter drugs; OTC